Role of Hyperbaric Oxygenation Plus Hypofractionated Stereotactic Radiotherapy in Recurrent High-Grade Glioma - Arpa, Donatella; Parisi, Elisabetta; Ghigi, Giulia; Cortesi, Annalisa; Longobardi, Pasquale; Cenni, Patrizia; Pieri, Martina; Tontini, Luca; Neri, Elisa; Micheletti, Simona; Ghetti, Francesca; Monti, Manuela; et al. (Frontiers in Oncology, 2021)
Background: The presence of hypoxic cells in high-grade glioma (HGG) is one of major reasons for failure of local tumor control with radiotherapy (RT). The use of hyperbaric oxygen therapy (HBO) could help to overcome the problem of oxygen deficiency in poorly oxygenated regions of the tumor. We propose an innovative approach to improve the efficacy of hypofractionated stereotactic radiotherapy (HSRT) after HBO (HBO-RT) for the treatment of recurrent HGG (rHGG) and herein report the results of an ad interim analysis. Methods: We enrolled a preliminary cohort of 9 adult patients (aged >18 years) with a diagnosis of rHGG. HSRT was administered in daily 5-Gy fractions for 3-5 consecutive days a week. Each fraction was delivered up to maximum of 60 minutes after HBO. Results: Median follow-up from re-irradiation was 11.6 months (range: 3.2-11.6 months). The disease control rate (DCR) 3 months after HBO-RT was 55.5% (5 patients). Median progression-free survival (mPFS) for all patients was 5.2 months (95%CI: 1.34-NE), while 3-month and 6-month PFS was 55.5% (95%CI: 20.4-80.4) and 27.7 % (95%CI: 4.4-59.1), respectively. Median overall survival (mOS) of HBO-RT was 10.7 months (95% CI: 7.7-NE). No acute or late neurologic toxicity >grade (G)2 was observed in 88.88% of patients. One patient developed G3 radionecrosis. Conclusions: HSRT delivered after HBO appears to be effective for the treatment of rHGG, it could represent an alternative, with low toxicity, to systemic therapies for patients who cannot or refuse to undergo such treatments.